2006
DOI: 10.2217/14622416.7.6.813
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B Locus in Caucasian Patients with Carbamazepine hypersensitivity

Abstract: HLA-B*1502 does not seem to be a marker for all forms of CBZ-induced hypersensitivity in a Caucasian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(152 citation statements)
references
References 21 publications
4
140
0
8
Order By: Relevance
“…On the other hand, a protecting effect of HLA has been suggested. Alfirevic et al 29 reported a potential protecting effect of HLA-B*0702 against carbamazepine-induced severe cutaneous adverse reactions in Caucasian patients. Functional studies together with genomic approaches are required for further progress in understanding the pathogenesis of ADR.…”
Section: Future Perspective Of Pharmacogenomics In Cutaneous Adrmentioning
confidence: 99%
“…On the other hand, a protecting effect of HLA has been suggested. Alfirevic et al 29 reported a potential protecting effect of HLA-B*0702 against carbamazepine-induced severe cutaneous adverse reactions in Caucasian patients. Functional studies together with genomic approaches are required for further progress in understanding the pathogenesis of ADR.…”
Section: Future Perspective Of Pharmacogenomics In Cutaneous Adrmentioning
confidence: 99%
“…[62] Buna karşın beyaz ırkta benzer birliktelik anlamlı görülmemiştir. [63] Medikal namaması nedeniyle yeni mekanizmalar ve hipotezler savunulmaya başlanmıştır. Rogawski ve Johnson, yakın zamanda ilgi çekici epidemiyolojik bulguları değerlendiren intrensek şiddet hipotezini ileri sürmüştür.…”
Section: İntrensek şIddet Hipotezi ("Intrinsic Severity Hypothesis")unclassified
“…Etnik kökenin, HLA allelleriyle ilişkili olmasından dolayı ilaçlara bağlı gelişen İHSS, bazı toplumlarda daha sık görülebilmektedir. HLA-B 1502 allelinin sık görüldüğü uzakdoğu ülkelerinde karbamazepine bağlı fatal İHSS olgularının sık görüldüğü bildirilmiştir (11).…”
Section: Resim1bilateral Tonsillerde Hipertrofi Ve Kriptlerunclassified